Detection of burned regions in the state of Tocantins-Brazil through image segmentation - Noleto, Fernando Barroso; Oliveira, Ary Henrique Morais de; Silva, Warley Gramacho da; Botelho, Glenda Michele (International Journal of Advanced Engineering Research and Science, 2019)
Burns in the Cerrado biome are recurrent problems in the state of Tocantins, located in northern Brazil. It is possible to observe, through satellite images, large areas that were destroyed by fire. This paper proposes an algorithm that automates the detection of burn regions in satellite images. In this algorithm, image segmentation techniques are used in order to detect regions that most resembles burned regions, considering color information. The results showed that the method can be effectively used to detect burned regions in satellite images.